Morfometria, alometria e assimetria flutuante do parasitoide de ovos Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) sob influência de inseticidas - Souza, Diego de (2017)
The morphometric study of parasitoids can help to understand the relationships between size and components that determine the quality when these organisms are produced in the laboratory, as well as to infer about efficiency as a biological controller. The interaction between insect size and abiotic components, eg insecticides, can also provide information on the consequences of the use of these substances. This work deals with morphometry, allometry and fluctuating asymmetry of parasitoids and the use as tools to evaluate components that determine the quality of these organisms. Due to the relationship between size and fitness of parasitoids, morphometry becomes relevant to evaluate the quality and infer about the potential of these organisms as biological controllers.